Quantitative EEG in "positive" and "negative" schizophrenia - Begić, Dražen (Array, 2000)
OBJECTIVE: Quantitative EEG has yielded different results in schizophrenia. The method of quantitative EEG has been relatively poorly used in the studies of the dichotomy into positive and negative schizophrenia. METHOD: Amplitude values of any particular frequency band (after fast Fourier transformation, FFT) were observed in 47 schizophrenic patients (25 patients with positive and 22 patients with negative schizophrenia) and in 50 normal subjects. The frontal, temporal, parietal and occipital regions (F3, F4, C3, C4, T3, T4, P3, P4, O1 and O2) were observed. RESULTS: Positive and negative schizophrenia were found to differ only in the delta and theta bands over frontal regions. Positive and negative schizophrenic patients were found to differ from normal subjects in delta, theta, alpha and beta 2 bands. CONCLUSION: Delta and theta activity may play a role as a marker in differentiating between positive and negative schizophrenia.